Application Of Play-Based Learning Model In Front Of Early Childhood Language Development - Beti Fadila Tapen; Fany Sarci Herlinda Nome; Seriyana Karlau; Myriam Stifania Tamelab; Yumida Maria Ora; Amida Riapa Nadila Nenohai; Fredericksen Victoranto Amseke (FKIP UNSULTRA, 2026)
Background: Language development is a fundamental aspect of early childhood education because it enables children to communicate, express ideas, and interact effectively with others. Play-Based Learning has been widely recognized as a developmentally appropriate approach that promotes meaningful learning through active participation and social interaction. Objective: This study aimed to examine the effect of the Play-Based Learning model on the language development of children aged 5–6 years at Cemara Liliba Kindergarten, Kupang City. Method: This quantitative study employed an ex-post facto research design involving 25 children selected through total sampling. Data were collected using validated psychological scales measuring the implementation of Play-Based Learning and children's language development. The data were analyzed using descriptive statistics and simple linear regression with SPSS version 25.0. Results: The findings revealed that Play-Based Learning had a positive and significant effect on children's language development (F = 11.498; p = 0.002 < 0.05). The coefficient of determination (R² = 0.324) indicated that the model explained 32.4% of the variance in children's language development, while 67.6% was influenced by other factors outside this study. Novelty: This study provides empirical evidence supporting the effectiveness of Play-Based Learning in enhancing language development within an authentic kindergarten context. Conclusion: Play-Based Learning significantly supports children's language development by encouraging meaningful interaction, communication, and active engagement. Teachers are encouraged to integrate storytelling, role-playing, educational games, and collaborative play into classroom activities to optimize children's language skills.